Buddhist Perspective on Politics [Public Lecture] - Dhajavanto, Bhikkhu (Journal of Political Science, 2023)
This is a public lecture delivered in a symposium jointly organized by the Surya Ratna Shakya Foundation, Pokhara and the Department of Political Science, Prithvi Narayan Campus, Pokhara on September 20, 2022.